Q: 4x2

Write your answer...

Submit

Related questions

4x2-81

12x * 4x2 = 48x3

4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x

4x2 + x2 = 8 + x2

sqrt(4x2) = Â± 2x

The GCF is 4x2.

1x8 2x4 4x2 4x2

4x2 - 2x = 0

2003 4x2 Gator

4x2=12

4x2 - 9y Not factorable from what I see.

4x2-y2 = (2x-y)(2x+y)

4x2 = 8, 8-9 = -1 therefore the answer is "-1"

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

In real numbers there is no square root of -4x2 However, when using complex numbers where √-1 = i, then: √-4x2 = 2xi If you were asking, for example, with regard to the difference of two squares, eg y2 - 4x2, then you are actually finding the square root of 4x2 which is 2x, giving: y2 - 4x2 = (y + 2x)(y - 2x)

If that's + 4x2, the answer is 2x(x2 + 2x - 4)

no

4x2-x+2x2 is 6x2-x when simplified

4x2-2x-12 = (2x+3)(2x-4)

y=4x2+3x+8

4x2-4x+1 = (2x-1)(2x-1)

4x2 plus 3=11

4x2+2x+1

4x2 - 23xy + 15y2 = (4x - 3y)(x - 5y)

The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).

Study guides